Police-public trust: toward amore complete perspective - Wise, Richard A. (Behavioral science & policy, 2025)
Most discussion of the police–public relationship focuses on the public’s lack of trust inpolice. Our research suggests that police trust in the public is another important factor inthis relationship and that addressing trust concerns on both sides may improve it. Weconducted two studies of police trust in the public. The results suggested that the morepolice trust the public, the more constructive risks they take in performing their jobs.Based on our results, we highlight the importance of reciprocity and attempting tosimultaneously increase both police and public trust to improve their relationship.Measures developed for these studies may inform future research on police trust in thepublic and develop interventions to improve it.